Extraction efficiency and activity determinants of soybean urease for sustainable biomineralization technology - Yuyuan Chen; Hemanta Hazarika (Smart Construction and Sustainable Cities)
Abstract Sustainable biomineralization technologies rely on the efficient hydrolysis of urea, typically catalyzed by urease-producing microorganisms or purified enzymes. However, conventional approaches such as microbially induced calcium carbonate precipitation (MICP) and enzyme induced calcium carbonate precipitation (EICP) face limitations related to biosafety risks and high costs, respectively. In this study, soybean, an abundant and low-cost agricultural resource, was utilized to extract urease through a soaking and centrifugation process. A geometric modeling approach using tri-axial ellipsoid theory was introduced to explain how soybean grain size affects sieved powder yield. The effects of soybean grain size, powder concentration, temperature, pH, and storage conditions on the urease activity were systematically evaluated. Results showed that smaller soybean particle sizes resulted in lower extraction efficiency, whereas medium-grain soybeans provided the most cost-effective source due to their higher sieved powder yield and lower market price. Urease activity was positively correlated with both powder concentration and temperature within the tested range and reached its maximum at approximately pH 8. Additionally, storage at 4 °C significantly preserved the enzyme's initial activity over 72 h compared to room temperature conditions. These findings establish a practical foundation for the cost-effective production of plant-derived urease, promoting broader application of biomineralization techniques in sustainable geotechnical engineering.